Four rare extranodal sites seen on FDG PET/CT in a single patient of disseminated lymphoma - Ameya D Puranik; Archi Agrawal; Nilendu C Purandare; Sneha Shah; Venkatesh Rangarajan (Indian Journal of Medical and Paediatric Oncology)
Extranodal disease refers to lymphomatous infiltration of anatomic sites other than lymph nodes. With the advent of FDG PET/CT for staging, rare sites of extranodal disease have been documented. We report a case of Non- Hodgkin′s lymphoma with four rare extranodal sites, namely adrenal, peripheral nerves, pancreas and prostate, in the same patient, detected on FDG PET/CT imaging.